(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Handloom industry is the most important cottage industry in Bangladesh but many of the handloom weavers are in vulnerable situation. Poverty and food security are intricately interlinked and it should be analyzed in different dimensions. This study was conducted to assess the calorie intake level, determine the factors influencing calorie intake and identify the problems faced by the handloom weaver households in a selected area of Bangladesh. A sample size of 100 households was selected randomly from six villages. Data were collected through field survey by using pre-designed and pre-tested interview schedule. To assess the per person per day calorie intake level of the sample household’s members, the food consumption data of seven days was measured by standard value of 100 gm each food item. To determine the factor influencing calorie intake multiple regression analysis was carried out. Calorie intake level and food consumption scores were used to measure poverty and food security. According to calorie intake level 15 percent of the handloom weavers belonged to hardcore poor whose average calorie intake was 1698.13 k.cal, and 46 percent weaver belonged to absolute poor whose average calorie intake was 2078.36 k.cal, and the rest 39 percent of the respondents belonged to non-poor whose average calorie intake was 2251.77 k.cal. Food consumption scores unveiled that 6 percent weaver households had poor food consumption while 39 percent weaver households had borderline food consumption; 31percent had acceptable low food consumption and 24 percent weaver households had acceptable high food consumption. Income of the household and cultivable area have positive impact on calorie intake of the household’s members. Among the reported problems low wage rate was ranked the main problem faced by the handloom weavers. Bangladesh Handloom Board, government and non-government organizations, and institutions can take specialized policies for handloom weavers to reduce poverty and strengthen food security. J. Bangladesh Agril. Univ. 17(1): 80–85, March 2019